Diagnosis of Atherosclerosis by using digital image processing - Dr.Hazeem Baqer; Abdulkareem. S. Gumar; Baidaa M.Alsafy (University of Thi-Qar Journal, 2019)
In this paper propose a method for the diagnosis of atherosclerosis as if that was normal or abnormal arteries, it has been the use of neural network technology after making optimizations, filter and remove the impurities of the arteries. Samples were taken from a group of patients in Nasiriyah Heart Center disparate ages and both sexes, which was 110 samples were 60 of them training samples which showed the results of 100% and 50 of these samples were tested results showed 92%